2010
DOI: 10.1097/jpn.0b013e3181ec0c60
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Breastfeeding Among Pregnant Mothers and Fathers

Abstract: The respondents correctly answered 68% of the items related to breastfeeding knowledge. The most usual lack of knowledge concerned how to increase lactation, sufficiency of breast milk in hot weather, sufficiency of breast milk for 4 months after birth, and the need to pump the breasts after alcohol consumption. Differences in the breastfeeding scores existed when gender, parity, age, living with spouse, educational level, smoking, time of pregnancy and breastfeeding history were considered. The web-based surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…During the early postnatal period, breastfeeding by cannabis-using mothers actively transfers the principle psychoactive component of cannabis, ∆9-tetrahydrocannabinol (THC) and other cannabinoids to the developing infant, as the lipophilic nature of these cannabinoids results in concentrations in breast milk which are equal to or exceeding that found in the plasma of the user 7,8 . Importantly, this transfer may persist well beyond the intoxication period of the user due to the long half-life of THC in breast milk 9 , thus occluding the possibility of simply breastfeeding outside of the acute cannabis consumption period as is often done with alcohol consumption 10 . Therefore, understanding and disseminating data regarding the consequences of THC consumption during the breastfeeding period is paramount to public health in the evolving age of cannabis use.…”
Section: Introductionmentioning
confidence: 99%
“…During the early postnatal period, breastfeeding by cannabis-using mothers actively transfers the principle psychoactive component of cannabis, ∆9-tetrahydrocannabinol (THC) and other cannabinoids to the developing infant, as the lipophilic nature of these cannabinoids results in concentrations in breast milk which are equal to or exceeding that found in the plasma of the user 7,8 . Importantly, this transfer may persist well beyond the intoxication period of the user due to the long half-life of THC in breast milk 9 , thus occluding the possibility of simply breastfeeding outside of the acute cannabis consumption period as is often done with alcohol consumption 10 . Therefore, understanding and disseminating data regarding the consequences of THC consumption during the breastfeeding period is paramount to public health in the evolving age of cannabis use.…”
Section: Introductionmentioning
confidence: 99%
“…In a Finnish study was observed similar results. Laanterä et al [12] in their study that aimed to describe breastfeeding knowledge of childbearing parents including 123 pregnant mothers and 49 fathers verified that the respondents correctly answered 68% of the items related to breastfeeding knowledge.…”
Section: Lack Of Knowledge Related To Lactation Stimulationmentioning
confidence: 99%
“…Several studies reported that perceived inadequate milk supply was the most common reason for introducing formula feeding, and the most common problems encountered were fatigue, sore nipples, and engorgement. [12] [13] They suggested that breast engorgement and fatigue could be effectively managed with increased knowledge about positioning, alternating breasts with each feeding and resting when the baby rests. The participants inadequate lactation knowledge was demonstrated when they failed to mention the recognized indicators of breastfeeding problems, such as diaper count, listlessness of the baby, or failure to let down, as reasons for discontinuing breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the maternal and paternal learning interests during pregnancy were super imposable, except for learning needs associated with breastfeeding. In fact, mothers ranked breastfeeding learning needs as fourth most important, and fathers ranked it twenty-first [21].…”
Section: Introductionmentioning
confidence: 99%